2018
DOI: 10.1108/compel-06-2017-0256
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the unstable period-1 orbit (UPO-1) of DC–DC converters by extracting harmonic content

Abstract: PurposeThis study aims to predict the unstable period-1 orbit (UPO-1) of DC–DC converters and find analytical expressions to describe it. Design/methodology/approachNonlinear dynamical phenomena of a peak–current–mode controlled direct current–direct current (DC–DC) Boost converter are discussed briefly first. Then fast fourier transform (FFT) analysis of state variables under different dynamic states is provided, and the characteristic of the harmonic content in different states is summarized. Following thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In addition, Bertrand has shown that VHF or ultra-high frequency would lead to energy storage elements with fractional calculus characteristics, and the fractional component model can more accurately predict the equivalent series resistance and capacitance value of capacitors at high frequency operation (Bertrand et al , 2010). And in recent years, research on the fractional calculus and its applications in modeling fractional-order pulse-width modulated (PWM) DC-DC converters with operating frequency of kHz level, along with further analyzing the influences of fractional-order components on the converters’ characteristics, has been deeply conducted (Diethelm, 2010; Oustaloup, 2014; Fa-Qiang and Xi-Kui, 2013; Chen et al , 2017a; Chen et al , 2018; Wei et al , 2019; Jiang and Zhang, 2020). However, there are few studies on the modeling and analysis of fractional VHF converters.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bertrand has shown that VHF or ultra-high frequency would lead to energy storage elements with fractional calculus characteristics, and the fractional component model can more accurately predict the equivalent series resistance and capacitance value of capacitors at high frequency operation (Bertrand et al , 2010). And in recent years, research on the fractional calculus and its applications in modeling fractional-order pulse-width modulated (PWM) DC-DC converters with operating frequency of kHz level, along with further analyzing the influences of fractional-order components on the converters’ characteristics, has been deeply conducted (Diethelm, 2010; Oustaloup, 2014; Fa-Qiang and Xi-Kui, 2013; Chen et al , 2017a; Chen et al , 2018; Wei et al , 2019; Jiang and Zhang, 2020). However, there are few studies on the modeling and analysis of fractional VHF converters.…”
Section: Introductionmentioning
confidence: 99%